Kashmiri People’s Perspective of Leech Therapy in view of Religious and Unani System of Medication - Bilal Ahmad Bhat; Syed Sabahat Ashraf; Ifrah Rashid; Ronika Yousuf; Fiba Arif; Qazi Nusrat; Aasiya Hamid; Intizar Ahmad (LECTURES: Journal of Islamic and Education Studies, 2024)
The Unani System of Medication is based on four therapeutic modalities namely, Regimental therapy, Dieto-therapy, Pharmacotherapy and Surgery. One of the most important and world wide practised methods of regimental therapy utilized for local evacuation of morbid humours is Irsale Alaq (Leech or Hirudo therapy). It is a procedure of treatment with the use of medicinal leeches which has been suggested and successfully practised by Greeko-Arab physicians since long in the management of various diseases such as musculoskeletal diseases, gynaecological disorders, chronic skin diseases, thromboembolic diseases, varicose veins, ENT disorders. Kashmir is a Muslim majority region and as per Islamic ruling leech therapy is permissible so any Halal treatment in Shariah perspective is accepted in Kashmir. In present study, we chose 100 respondents at random on their consent and with the help of self-developed questionnaire collected information on the topic understudy. The study revealed that Kashmiri people consider leech therapy a traditional /religious treatment and use leech therapy for treatment of many diseases such as to treat frost bite, Chronic skin ailment, sports/accident injuries, Musculoskeletal pain, Hypertension, Sinusitis, Osteoarthrites, Migraine. Majority of respondents recommend leech therapy for people for treatment of various common ailments in Kashmir as they believe its less costly, effective and traditional method of treatment of diseases like Frostbite, sports injuries, arthritis. Statistically, significant difference was observed between male and female respondents for treating various ailments using leech therapy (P<0.05). Further, statistically non significant difference between male and female respondents in leech therapy satisfaction level was observed (P>0.05). In Kashmir like in many Muslim countries a good number of people prefer leech therapy to cure many ailments because of its medical importance. Finally, group discussion with elders and leech healers revealed that one should consult an expert/Doctor before going for leech therapy and in case there is some side effect after leech therapy.